Contribution of dps to Acid Stress Tolerance and Oxidative Stress Tolerance in Escherichia coli O157:H7 - Choi, Sang Ho (American Society for Microbiology, 2000)
An Escherichia coli O157:H7 dps::nptI mutant (FRIK 47991) was generated, and its survival was compared to that of the parent in HCl (synthetic gastric fluid, pH 1.8) and hydrogen peroxide (15 mM) challenges. The survival of the mutant in log phase (5-h culture) was significantly impaired (4-log(10)-CFU/ml reduction) compared to that of the parent strain (ca. 1.0-log(10)-CFU/ml reduction) after a standard 3-h acid challenge. Early-stationary-phase cells (12-h culture) of the mutant decreased by ca. 4 log(10) CFU/ml while the parent strain decreased by approximately 2 log(10) CFU/ml. No significant differences in the survival of late-stationary-phase cells (24-h culture) between the parent strain and the mutant were observed, although numbers of the parent strain declined less in the initial 1 h of acid challenge. FRIK 47991 was more sensitive to hydrogen peroxide challenge than was the parent strain, although survival improved in stationary phase. Complementation of the mutant with a functional dps gene restored acid and hydrogen peroxide tolerance to levels equal to or greater than those exhibited by the parent strain. These results demonstrate that decreases in survival were from the absence of Dps or a protein regulated by Dps. The results from this study establish that Dps contributes to acid tolerance in E. coli O157:H7 and confirm the importance of Dps in oxidative stress protection.